PENDIDIKAN BERBASIS MANAGEMEN MUTU TERPADU (MMT).doc - Munawir Husni (Fakultas Tarbiyah Institut Agama Islam Hamzanwadi NW Pancor, 2016)
The insistence to improve the quality of education is always appearing, especially the government. Almost at every opportunity and meetings, the central government itself has always urged all parties, in particular the apparatus of education providers to increase the quality of education is improved. Simultaneously, people also ask the central government to act swiftly. Seeing behavior and a strong response from each participant, to show how quality improvement becomes necessary and urgent to do. But in reality, many years this issue is encouraged, until recently the “ quality of education” is still bad in anywhere. What has caused it happened actually ? This is the substance that want to try to be explored in order to find a solution. Integrated Quality Management (MMT) is one of the alternative concept to overcome this problem. Although it must be recognized a problem occurs and certainly appears.